(untitled) (Journal of Nobel Medical College, 2014)
The success of removable orthodontic appliance mainly depends upon good retention of the appliance. Adequate retention of a removable orthodontic appliance is achieved by incorporating certain wire components, called clasp, which engages the undercuts on the teeth. Clasps are the retentive components of removable orthodontic appliances. There are various designs of clasps advocated for various clinical situations. This article presents an overview of various clasp designs with advantages and disadvantages of each type and their uses in particular clinical situations. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.10046 Journal of Nobel Medical College Vol.3(1) 2014; 1-9